(untitled) (Latakia University Journal -Medical Sciences Series, 2024)
Aim: This study was designed to examine the efficacy of utilizing the Posterior tonsillar pillar in management of velopharyngeal insufficiency symptoms. Material and methods: The research sample consisted of 10 patients who had an operation to correct velopharyngeal insufficiency using the posterior tonsillar pillar. The study variables were the improvement of patient intelligibility speech, the elimination of snoring and nasopharyngeal regurgitation, the patient’s satisfaction and the condition of the middle ear before surgery and after 12 months post-operatively. Results: The patients’ speech improvement reached 61.91%. No snoring or nasopharyngeal regurgitation occurred postoperatively. The condition of the middle ear 12 months after surgery with a tympanometry test type A (normal) in 40% of patients, while type B (inflammation and fluid in the ear) in 60% of patients. Patient satisfaction scored 8 out of ten for 80% and 7 for 20% of patients. Conclusion: The use of the posterior tonsillar pillar showed effectiveness in improving subsequent speech, eliminating nasopharyngeal regurgitation and snoring, and an asymptomatic middle ear condition in all patients, and very good patient satisfaction postoperatively.